DAMPAK COVID-19 TERHADAP KESEJAHTERAAN MASYARAKAT DESA PENGLIPURAN KECAMATAN BANGLI KABUPATEN BANGLI - Bagiana, I Gusti Bagus Yogi Sutanegara; Bendesa, I Komang Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024DO - 10.24843/EEB.2024.v13.i06.p15, 2024)
The aims of this study to analyze differences in the welfare of the people after the Covid-19 outbreak, also to analyze the survival strategy of the community during the Covid-19 pandemic in Penglipuran Village, Bangli District, Bangli Regency. The population of this study is the head of the family of the Penglipuran Village community which in 2021 amounted to 233 families, with a sample of 70 respondents calculated using the sampling method used is non-probability sampling, namely a combination of accidental sampling and snowball sampling. The test in this study uses parametric statistics, namely testing using the paired sample t-test method with the STATA 15 application. The results of this study are that there are differences in the welfare of the community in Penglipuran Village, Bangli District, Bangli Regency after the Covid-19 which can be seen from the differences in opportunities Community Work and Income in Penglipuran Village before and after the Covid-19 Pandemic. The survival strategy of the community in Penglipuran Village, during the Covid-19 pandemic, is to switch professions from those who originally worked as a tourism support sector, such as traders or tourism managers, then switched professions to become farmers.